Place of Executive Authorities in the Realization of the Right to Freedom of Peaceful Assembly - M. A. Sambor (Bulletin of Kharkiv National University of Internal Affairs)
The issue of realizing the right to freedom of peaceful assembly is one of the most pressing and problematic issues in the development of democratic relations in society. Since the realization of the right to freedom of peaceful assembly implies that the subject of realizing this right has a duty to notify, the purpose of this article is to determine the place of executive authorities while notifying the intention to the realization of the right to freedom of peaceful assembly.